Інтелектуальна інформаційна система автоматичної генерації новин - Василюк, Андрій; Гришканич, Роман (Видавництво Львівської політехніки, 2017)
Intelligent system of automatic news generation able to provide high quality, truthful and actual updates of content for web site, that significantly simplify the work of site editor. Well-designed administration panel allow easy to manage the information system of the people who do not have knowledge in web development. With the obtained results, we can significantly increase traffic to your site, that will give more profits.
Keywords: інформаційна система; інтелектуальна система; інтернет новини; генерація новин; шаблон; нейронні мережі; парсинг даних; веб-розробка